Reality of Implementing Electronic Management and the ways of Developing from The Principals Perspective’s - Al- Jaber, Sultan Suleman (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the Reality of Implementing Electronic Management and The ways of Developing from The Principals Perspective’s in High School In the Jordanian Middle Badia/ Al- Jezah restrict study sample consisted of (33) male principals and(32) female principals. To achieve the objectives of the study، a questionnaire was used as a tool for data collection; it consisted of (29) paragraphs، distributed into Three areas:("reality of implementing E- management" The degree was scored a moderate with the percentage weight of(2.77)، "Level of electronic Education" The degree was scored a moderate with the percentage weight of(2.37) "Suggestion to developing E- Management" The degree was scored a moderate with the percentage weight of(3.62) ). The result showed that the level of reality of implementing E- management was moderate. In light of these findings, the researcher suggested set recommendations including spreading the cultural E- Management، Develop annual plans for training programs.